CO19 | Hypercoagulability in wild-type transthyretin amyloidosis: evidence from whole blood thromboelastometry (Bleeding, Thrombosis and Vascular Biology)
Background and Aims: Thromboembolic events are a well-recognized complication of wild-type transthyretin amyloidosis (ATTRwt), with reported prevalence ranging from 6% to 28%. Atrial fibrillation (AF), mechanical atrial dysfunction, and systemic myopathy have been identified as major contributing factors. However, thromboembolic events have also been reported in patients in sinus rhythm and in those receiving adequate anticoagulant therapy, suggesting intrinsic prothrombotic mechanisms may also be at play. This study aimed to compare conventional coagulation parameters and whole blood thromboelastometry (ROTEM) profiles between patients with ATTRwt and age- and sex-matched healthy controls, to identify potential hypercoagulable features independent of AF or anticoagulation therapy.